Inquiry into the use of online communication for teacher reflection - Harkrider-Friedman, Nancy. (2008)
This qualitative inquiry investigates two groups of Singapore pre-service teachers' recall of "critical teaching events" as reflection-on-action in the socially constructed space of Computer-Mediated Communication. The inquiry was not designed nor does it purport generalizations about communications within on-line reflective environments. Instead, it provides transferable insights as illuminative experience since "by studying the uniqueness of the particular, we come to understand the universal" (Simons, 1996, p. 231). Following a pilot study, which served as grounding for an extended engagement, the inquiry was actualized as an extended case study of specific on-line reflective experience. The multi-method analysis approach to triangulation in the extended engagement was possible because of the depth and richness of data in the extended engagement and was a proactive response to the immature and often conflicting theoretical domain of Computer-Mediated Communication. Selected analysis methods include detailed documentation of the levels of reflective evidence, analysis of one overarching corollary, three supporting corollaries and one discovered corollary as patterns of reflective interaction, participant perceptions of the experience, as well as the researcher's journals as an extended reflection on the four year inquiry. Analysis was oriented to transparency, using accepted qualitative criteria for credibility, originality, transferability and internal validity, addressed through peer review.